Occurrence of Prostenorchis elegans in the San Martin titi monkey (Plecturocebus oenante) reinserted in the tropical forest of the national park Coordillera Cerro Escalera, San Martin Region - López F., Alicia (2021)
It is reported the case of an adult titi monkey (Plecturocebus oenante) parasitized with Prosthenorchis elegans, which died at the end of December 2019. The animal was in a wildlife rescue centre located on the banks of the Shilcayo Quebrada, the entrance gate of the national park "Cordillera Escalera", in San Martín, Peru. The animal, living in semi-captivity, did not show clinical signs, but it collapsed from a height of 5 m. At necropsy, abdominal exudate, perforation at the level of the small intestine, congestion of blood vessels and mesenteric lymphadenopathy, nodulations in the intestinal wall and a severe infection of white and round parasites were evidenced. The coproparasitological examination revealed characteristic eggs of the genus Prosthenorchis and the analysis of the adult parasite revealed the cranial hooks and characteristic structures of the species Prosthenorchis elegans, a parasite found in neotropical primates. This case is reported not as an accidental necropsy finding, but one which cause of death was as a consequence of septic shock due to a generalized peritonitis caused by a severe parasitic infection of this Acantocephalus that generated an intestinal perforation.